GAMBARAN MIKROSKOPIS Pediculusis humanus capitis SANTRI PUTRI DI PONDOK PESANTREN DI BANGKILING RAYA TAHUN 2026 - Nurbidayah Nurbidayah; Siti Alfia Zulhida; Nafila; Bio Putri Ayanti (Klinikal Sains : Jurnal Analis Kesehatan, 2026)
Pediculosis capitis is the presence and development of parasites caused by Pediculus humanus capitis, which infest the scalp and are commonly known as head lice. This study aimed to determine the microscopic characteristics of Pediculus humanus capitis and the characteristics of respondents based on age, educational level, and personal hygiene among female students at an Islamic boarding school in Bangkiling Raya in 2026. This research employed a descriptive design with a cross-sectional approach. The study population consisted of female students living in the dormitory, and 35 respondents were selected using a purposive sampling technique. Samples were collected by combing the hair with a fine-toothed lice comb, and microscopic examinations were conducted at the Banua Lawas Community Health Center Laboratory. The results showed that 22 respondents (63%) were positive for Pediculus humanus capitis, while 13 respondents (37%) were negative. The respondents' characteristics indicated that the majority were aged 11–15 years (51%), most were junior Islamic secondary school (MTs) students (77%), and 51% had good personal hygiene. Microscopic examination successfully identified adult lice and nits based on their characteristic morphological features. Health education is needed to reduce the incidence of pediculosis capitis in the Islamic boarding school environment.